Mars’ ionosphere: The key for systematic exploration of the red planet - Sánchez-Cano, Beatriz (Frontiers in Astronomy and Space Sciences, 2023)
The near three decades of continuous Mars' exploration has opened the door to the understanding of the Martian space environment, which includes the solar wind, magnetosphere, ionosphere and atmosphere, and is a complex structure with simultaneous downward and upward couplings. However, we do not yet understand many of the physical processes that drive matter and energy flow between these couplings and within the various atmospheric reservoirs (including temporal and spatial changes on short time scales). Although each coupling plays an essential role for the system, understanding the fate of the ionosphere, as a natural sink of both internal (i.e. atmospheric cycles) and external (i.e. solar wind) energy inputs, is the key for a successful future systematic exploration of Mars.